Effect of ultrasonic vibration on microshear bond strength of flowable composite to enamel - Ebrahimi Nezhad, Mahtab; Jafarpour, Dana; Gholamrezaei Saravi, Mahdi (Brazilian Dental Science, 2020)
Objective: The present study aimed to assess the influence of vibration effect on microshear bond strength (µSBS) of flowable composite to enamel. Material and Methods: Sixty non-carious extracted human premolar teeth were collected and randomly divided into six groups (n = 10) after being trimmed to produce a smooth flat surface: Flowable composites [Wave (SDI), Wave HV (SDI) and Grandioflow (Voco)] were used as bonding agents without or with vibration using an ultrasonic scaler (Mini Piezon, EMS, Switzerland). Composite resin, with an internal diameter of 0.7mm and height of 1mm, was cured on the substrate. The specimens’ µSBS was tested by a microtensile tester (Bisco, USA) at a crosshead speed of 0.5 mm/min. The bond strength values were analyzed using one-way ANOVA and post hoc Tukey test (p < 0.05). Results: Vibration did not lead to any significant difference in the µSBS values of Wave, Wave HV, and Grandio Flow µSBS values (P=0.690, P=1.000 and P=0.947, respectively). No significant difference was found between flowable composites in terms of micro shear bond strength to enamel (p > 0.05). Conclusions: The application of ultrasonic vibration might not be advantageous in terms of improving the shear bond strength of flowable composites to enamel.KEYWORDSBond strength; Enamel; Flowable composite; Ultrasonic; Vibration.